Comparison of plasma fetuin A levels in patients with early-onset pre-eclampsia vs late-onset pre-eclampsia. (May 2016) - Sanhal, C.Y.; Can Kavcar, M.; Yucel, A.; Erkeneklı, K.; Erkaya, S.; Uygur, D.
Abstract: Objective: Pre-eclampsia (PE) is among the most commonly researched topics in perinatology. Fetuin-A (FA), a multifunctional protein, has roles in the inhibition of ectopic calcification and the regulation of serum glucose levels. Reduced FA is an indicator of inflammation. This study was performed to investigate the potential role of inflammation in the pathophysiology of early- and late-onset PE by measuring FA levels. Study design: In total, 110 patients were included in this study. Early- and late-onset PE were defined as a diagnosis at <34 weeks or ≥34 weeks of gestation, respectively. Plasma FA levels were determined by immunoassay, which was performed in duplicate using a sandwich enzyme-based technique. Parametric data were appraised using an independent two-sample t -test, and non-parametric data were compared using the Mann–Whitney U -test. Multivariate logistic regression was performed to investigate the impact of certain parameters on PE. Receiver operating characteristic analysis was used to evaluate the diagnostic performance of FA. Results: There were 24 patients with early-onset PE and 19 gestational-age-matched controls. Plasma FA levels were significantly lower in the early-onset PE group compared with the controls (17.3 ± 3.3 ng/ml vs 21.4 ± 3.5 ng/ml, p < 0.05). There were 36 patients with late-onset PE and 31 gestational age-matched controls. Plasma FA levels were significantly higher in the late-onset PE group compared with the controls [26.1 ng/ml (range 13.4–52.0) vs 18.4 ng/ml (range 14.9–24.9), p < 0.05]. Besides the parameters used in the diagnosis of PE, the single most important variable related to PE was FA. The optimal cut-off level for FA in the prediction of early-onset PE was 19.6 ng/ml [sensitivity 79%, specificity 83.3%, area under the curve (AUC) 0.796, 95% confidence interval (CI) 0.650–0.943, p = 0.001]. FA did not show a statistically discriminative value in differentiating late-onset PE from control subjects (AUC 0.196, 95% CI 0.085–0.306). Conclusion: Early- and late-onset PE were associated with lower and higher levels of FA, respectively. A relationship was found between inflammation and early-onset PE but not late-onset PE.